Is first trimester exposure to the combination of antiretroviral therapy and folate antagonists a risk factor for congenital abnormalities?. Issue 6 (1st December 2001) - Jungmann, Eva M; Mercey, Danielle; DeRuiter, Annemiek; Edwards, Simon; Donoghue, Sheila; Booth, Tamsin; Mohan, Depeeka; Lyall, Hermione; Taylor, Graham P
Abstract : Objectives: To assess use of antiretroviral therapy (ART) by HIV positive pregnant women in London since 1994 and the risk of congenital abnormalities associated with multidrug exposure during the first trimester of pregnancy. Methods: Retrospective multicentre study of medical, obstetric, and paediatric notes of all mother-infant pairs, where the mother was known to be HIV infected before delivery, using a standardised proforma. Results: In this study of 195 mother-infant pairs, use of ART during any stage of pregnancy increased from 33.3% in 1994 to 92.5% in 1999 (p=0.01, trend). First trimester exposure increased from 0% in 1994 to 27.5% in 1999 (p=0.00045, trend). Congenital malformations were observed in nine infants (4.6%). Compared with infants not exposed to ART or folate antagonists during the first trimester (n=148), exposure to both ART and folate antagonists during the first trimester (n=13) was associated with an increased risk of congenital abnormalities (4% v 23.1%; OR 7.10, 95% CI 1.5, 34.2). No malformations were observed in the 34 children exposed to either ART or folate antagonists alone during the first trimester. Conclusion: An increasing number of HIV infected women conceived while on ART. Although there is no evidence of teratogenicity caused by ART if given alone during the first trimester, exposure to the combination of ART and folate antagonists was associated with a significantly higher risk of congenital abnormalities in this cohort.